The Impact of Environment-Based Education on Students' Vocabulary Development at Junior High School - Laoli, Adieli; Fristaniat Zendrato, Agnes; putri Telaumbanua, Inayah syah; Desna yarlina Telaumbanua; Danieli Gea (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the effects of environment-based education on students' mastery of vocabulary at Junior High School. English, recognized as a global language, is essential for both educational and career advancement. However, Indonesian students often struggle with vocabulary acquisition. To evaluate how the integration of environmental elements into English learning can enhance vocabulary skills, this research adopts a qualitative approach. It employs observation, interviews, and documentation as key methods of assessment. The study involved an English teacher and 23 seventh-grade students, with a sample of 15 students selected for the research. The findings reveal that students faced challenges in retaining vocabulary due to conventional teaching methods and insufficient exposure to context. However, after introducing environment-based learning—where students observed and described objects in their school surroundings—they showed remarkable progress in vocabulary retention, comprehension, and application. This approach not only boosted their language skills but also heighted their motivation, engagement, and awareness of the environment. Overall, the results indicate that environment-based education is an effective strategy for enhancing vocabulary mastery, making the learning experience more meaningful and relevant to students' everyday lives.